A Method for Incorporating Live Load Reduction Provisions in Frame Analysis - Ziemian, Ronald D.; McGuire, William (Engineering Journal, 1992)
The effects of live load are often reduced to reflect the low probability of all live load existing simultaneously throughout a substantial portion of a structure. An approach for incorporating live load reduction provisions within system analyses is presented. By determining an appropriate applied live load, the resulting forces in both the beams and the columns will include the ASCE 7-88 live load reduction provisions. In applying this live load, any displacements calculated by a structural analysis will be consistent with the reduced internal member force Distribution. Joint equilibrium will be maintained. Because the procedure does not rely on applying the principle of superposition, it may be used with either linear or nonlinear structural analyses.